ChemInform Abstract: 4, 4′‐Bithiazole‐Based Tetraarylenes: New Photochromes with Unique Photoreactive Patterns. Issue 2 (9th January 2013) - Gavrel, Gildas; Yu, Pei; Leaustic, Anne; Guillot, Regis; Metivier, Remi; Nakatani, Keitaro
Abstract Title compounds (I) bearing an 1, 3, 5, 7‐octatetraene photoreactive backbone are synthesized and their photochromic behavior is investigated.